Civil Society Organization and Community Development, a Study of Enugu North Senatorial District of Enugu State. Nigeria (2007-2019) (International Journal of Innovative Research in Engineering & Management, 2022)
Civil society organization and community  development A study of Enugu north senatorial district of  Enugu State (2007-2019). This study adopted three specific  objectives: to ascertain the contributions of civil society  organization to community road infrastructural  development, to establish the linkage between civil society  interventions and availability of potable water supply, and  to examine the effect of civil society organizations activities  in the improvement of community primary healthcare in  Enugu North Senatorial District, Diffusion of innovation  theory is the theoretical framework of analysis. Survey  design utilized with population of 1,660,000 and sample  size of 400. Data generated from primary and secondary  sources. Descriptive statistics were used for data analysis  and hypotheses were tested with chi-square with the aid of  SPSS. The major findings are; civil society organization  does contribute positively to community road infrastructural  development, there is linkage between civil society  organization and availability of potable water supply in  Enugu north senatorial district and civil society  organization’s activities in Enugu north senatorial district  did improve community primary healthcare significantly in  Enugu north senatorial district. This study concludes that  the citizens and other stakeholders are enjoined to advance  the course of CSO’s activities towards community  development for the betterment of the communities, states  and the society at large. It was recommended that public  sector should make enabling laws that will guarantee  further engagement of various CSOs as development driver  of the state and government should sensitize the populace to  be actively involved in most CSO’s programmes.
Keywords: Civil Society Organization; Community; Development; Enugu North Senatorial District; Nigeria